Membangun Social Support Network melalui Penguatan Kapasitas Remaja Perempuan dalam Pencegahan Child Marriage di Perdesaan - Yun Fitrahyati Laturrakhmi; Fitri Hariana Oktaviani; Azizun Kurnia Illahi (Jurnal Gema Ngabdi, 2023)
This community service is intended to develop IPPNU members’ capacity in order to strengthen their function as social support networks among girls in Kecamatan Tutur, Kabupaten Pasuruan Jatim since the incidence rate of child marriage in this area has become higher due to covid-19 pandemic. The organization’s ability to function as a social support network becomes critical for enhancing self-agency among girls in rural areas regarding their decision to marry. In order to develop this function, a range of treatments had been accomplished to improve participants’ knowledge, skills, and ability to apply critical thinking in both exploring the causes and designing preventive measures for child marriage. By involving 11 IPPNU members as participants, this community service employed workshops as the main method. The results have shown that participants’ knowledge about child marriage has been improved, particularly by the use of participatory communication techniques to explore some issues through the victims’ lens. This activity also resulted in the enhancement of participants’ knowledge and concern to utilize an online application for designing and creating digital content. Another interesting finding is the fact that participants had performed critical thinking through their reflection on what would they contribute to their environment individually.